Estratégias de operações e práticas lean-green: um estudo de casos múltiplos em empresas do setor automotivo - Queiroz, Geandra Alves (2021)
The reduction of environmental impacts has increasingly been treated as a factor of competitive advantage by organizations. This reflects directly on the operational strategies of companies, making it necessary to include environmental performance as one of their competitive priorities. The integration of Lean Manufacturing and Green Manufacturing approaches has been pointed out as a key to improving the competitiveness of organizations because it is a way to equate the environmental priority with other competitive priorities. However, there are still no scientific articles that address all the content of operations strategy (competitive priorities and decision areas) when Lean and Green practices are implemented. In this context, the first step of this study consisted in conducting a systematic literature review presenting some of the main relationships between Lean and Green and the content of operations strategy and highlighting the occurrence of synergies or trade-offs between competitive priorities as well as changes in decision areas when Lean and Green practices are implemented. The results of this study pointed out that Lean and Green integration can promote synergies between competitive priorities, but it can also promote trade-offs between some competitive priorities, with the trade-off between cost and environment priorities being the most frequently mentioned. Furthermore, Lean is pointed out as a basis for the management of production systems, and green practices are generally used as a complement and to support the inclusion of the environment as a competitive priority. The second stage of this research was to conduct case studies in six companies in the automotive sector that implement Lean and Green practices, with the purpose of identifying the contents of their operations strategies. The results indicated that the companies attribute different levels of importance to the priority environment and have different levels of Lean and Green. In general, the companies consider that the Lean-Green approach generates synergies between priorities, with the trade-off between cost and environment being the only one addressed in the cases. It was confirmed that Lean can contribute to the reduction of environmental impacts reduction, especially regarding to resource consumption. Moreover, it was found that the companies that prioritize the environment more in their actions presented more changes in the decision areas. The crossing of the theoretical results with the empirical results allowed us to reinforce the theoretical propositions stated in this thesis. All the propositions formulated from the systematic literature review were illustrated in the cases studied and complemented with some questions.